Technical efficiency of public district hospitals in Madhya Pradesh, India: a data envelopment analysis - Tej Ram Jat; Miguel San Sebastian (Taylor & Francis Group, 2013)
Background: Scarcity of resources for healthcare is a well-acknowledged problem. In this context, efficient utilization of existing financial and human resources becomes crucial for strengthening the healthcare delivery. The assessment of efficiency of health facilities can guide decision makers in ensuring the optimum utilization of available resources. Objective: The objective of this study was to evaluate the technical efficiency (TE) of the public district hospitals in Madhya Pradesh, India, with special emphasis on maternal healthcare services, using data envelopment analysis (DEA). Methods: Data from 40 district hospitals from January to December 2010 were collected from the health management information system and other records of the department of health and family welfare of the state. DEA was performed with input orientation and variable returns to scale assumption. Results: TE and scale efficiency scores of the district hospitals were 0.90 (SD = 0.14) and 0.88 (SD = 0.15), respectively. Of the total district hospitals in the study, 20 (50%) were technically efficient constituting the ‘best practice frontier’. The other half were technically inefficient, with an average TE score of 0.79 (SD = 0.12) meaning that these hospitals could produce the same outputs by using 21% less inputs from current input levels. Twenty-six (65%) district hospitals were found to be scale inefficient, manifesting a mean score of 0.81 (SD = 0.16). Conclusions: Half of the district hospitals in the study were operating inefficiently. Decision makers and administrators in the state should identify the causes of the observed inefficiencies and take appropriate measures to increase efficiency of these hospitals.